2002
DOI: 10.1074/jbc.m106826200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of Smad1 and Smad4 to Two Distinct Motifs Mediates Bone Morphogenetic Protein-specific Transcriptional Activation ofId1 Gene

Abstract: Bone morphogenetic proteins (BMPs) are potent inhibitors of myoblast differentiation and inducers of bone formation both in vivo and in vitro. Expression of Id1, a negative regulator of basic helix-loop-helix transcription factors, is up-regulated by BMPs and contributes to the antimyogenic effects of this family of cytokines. In this report, we have identified a specific BMP-2 immediate early response enhancer in the human Id1 gene. Transcriptional activation of the enhancer was increased by overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
209
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(230 citation statements)
references
References 57 publications
16
209
1
4
Order By: Relevance
“…GC-rich boxes also differentially favor BMP activation in cell culture transfections and reporter gene induction is inefficient with SBE sites alone (Korchynskyi and ten Dijke, 2002;Katagiri et al, 2002;López-Rovira et al, 2002). Perhaps the similarity in in vitro affinities of isolated MH1 domains to DNA motifs does not accurately reflect the preferences of the full-length proteins complexed in R-Smad/Smad4 heterotrimers.…”
Section: It's a Smad World: Dna Recognition By The Smadsmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-rich boxes also differentially favor BMP activation in cell culture transfections and reporter gene induction is inefficient with SBE sites alone (Korchynskyi and ten Dijke, 2002;Katagiri et al, 2002;López-Rovira et al, 2002). Perhaps the similarity in in vitro affinities of isolated MH1 domains to DNA motifs does not accurately reflect the preferences of the full-length proteins complexed in R-Smad/Smad4 heterotrimers.…”
Section: It's a Smad World: Dna Recognition By The Smadsmentioning
confidence: 99%
“…This may explain why relatively long concatemers of Smadbinding sites are often needed to obtain transcriptional activation in cell culture (Jonk et al, 1998;. The promoters of some BMP inducible genes (e.g., bambi, and the id and vent family genes) have numerous Smad-binding sites (López-Rovira et al, 2002;Korchynskyi and ten Dijke, 2002;Karaulanov et al, 2004), presumably to more efficiently recruit the Smads to enhance transcriptional regulation. While isolated MH1 domains of Smad3 do not show cooperative binding to palindromic SBEs (Shi et al, 1998), it is reasonable to believe that full-length Smads would behave differently.…”
Section: It's a Smad World: Dna Recognition By The Smadsmentioning
confidence: 99%
“…We found that Smad2-null MEFs responded well to TGF-β1 to induce Smad3 phosphorylation and Id1 expression ( Figure 3C, lane 4). In addition, we included BMP2 as a control because it is a well-known inducer of Id1 expression [29,30]. As expected, BMP2 normally induces Smad1 phosphorylation and does not require Smad2 for Id1 induction ( Figure 3C, lane 2).…”
Section: Tgf-β1-dependent Id1 Induction Does Not Require Smad2mentioning
confidence: 99%
“…The BMP-responsive element of the Id1 promoter has been localized to a small fragment containing a cluster of SBE and binding sites of other transcription factors [29,30]. To determine the TGF-β1 responsive element in the Id1 promoter, we analyzed the ~2-kb sequence upstream of the transcriptional initiation site of the Id1 gene.…”
Section: Smad3 and Smad4 Bind To The Mouse Id1 Promotermentioning
confidence: 99%
“…This motif can also bind phosphorylated Smad1 in the presence of Smad4, and heterologous reporter genes containing concatamers of this sequence respond to BMP but not TGF␤/ activin signaling (10). A similar motif is responsible for BMP responsiveness of the mouse Smad6 and Id1 gene promoters (11)(12)(13). Other Smad binding elements include the sequence CAGAC, multimers of which are found in TGF␤-responsive promoter elements and are required for TGF␤ responsiveness (14 -16).…”
mentioning
confidence: 99%